Wakefield excitation and electron acceleration at detuning bunch repetition frequency and frequency of eigen principal mode of wakefield - Balakirev, V.A.; Onishchenko, I.N.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2013)
Theoretical results of process of the wake field excitation in the dielectric waveguide by sequence of relativistic bunches in the presence of detuning between the bunch repetition frequency and the frequency of the fundamental wave waveguide. In this case the wake waves radiated by individual bunches, there is the phase shift, and, beginning with some number of the bunch, the phase shift will be. The polarity of the field is changed and the subsequent bunches gain energy. Energy spectra of accelerated (decelerated) particles are obtained.